Drainage Handling System in Tambaloka City - I Gusti Lanang Made Parwita; Gede Yasada; Made Mudhina (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
A City which is lovable by the society is a livable city, productive and has good spirit TambolakaCity is the capital city of soutwest Sumba, like other cities which focuses alsoon the city itself towards the desirable community. Tambolaka city is a small city with an area of 9,605 acre has population about 19,241 people with an average population growth is 4% (Central Bureau of Statistics in Soutwest Sumba,2010). One of the basic urban infrastructure which is considered quite important in Tambolaka City is the sewerage of the drainage system of the city. A good city needs to consider the condition of the culverts because if the water is stagnant, it will geatly affect the life of the city i. e buildings become easily damaged, unhealthy environments, and dirty houses. The drainage systems in Tambolaka City include the trade area, offices, housing, and other areas. The rapid growth of the city is trying to be balanced by make urban infrastructure, one of which very important related to infrastucture is in ralation to drainage problems. The drainage conditions in the region are already organized to mitigate the effects of flooding and stagnant water, in some locations there are problems such as unavailability of drainage, inadequate of drainage, stagnant water, and so on.